EFFECTS OF FEEDING FREQUENCY ON THE GROWTH AND SURVIVAL OF CATFISH (CLARIAS MACROCEPHALUS GUNTHER) LARVAE - Mollah, M F A; Tan, E S P (Indian Journal of Fisheries, 2011)
Studies on the effects of feeding frequency on the growth and survival with 5-day old catfish [Clarias macrocephalus, Gunither) larvae of initial size ranging from 7.9 + 0.4 mm to 8.0 + 0.4 mm in total length were conducted in glass aquaria over a period of 28 days at an initial stocking density of 4 fish 1" . Four feeding frequencies in the order of five feedings, three feedings, two feedings and one feeding day " wiiitb live food Moina and/or Tubifex worms) were studied. Results indicated that a feeding frequency of three times day" was as good as that of five times when the growth of larvae in term of length-gain was compared. Larvae under the feeding frequency of five and three times day’ showed significantly (p < 0.05) higher growth and survival than those at two feedings and one feeding day" , The survival rate did not differ significantly at the feeding frequency of five and three times day" . A feeding frequency of three times day with live food was, therefore, appeared to be suitable for rearing catfish larvae at the ambient temperature which ranged between 26 and 31Â°C.